2012
DOI: 10.1016/j.neures.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic activity-induced Ca2+ signaling in avian cochlear nucleus magnocellularis neurons

Abstract: Neurons of the avian cochlear nucleus magnocellularis (NM) receive glutamatergic inputs from the spiral ganglion cells via the auditory nerve and feedback GABAergic inputs primarily from the superior olivary nucleus. We investigated regulation of Ca2+ signaling in NM neurons with ratiometric Ca2+ imaging in chicken brain slices. Application of exogenous glutamate or GABA increased the intracellular Ca2+ concentration ([Ca2+]i) in NM neurons. Interestingly, GABA-induced Ca2+ responses persisted into neuronal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Readers are referred to a comprehensive review covering these studies (Rubel and Fritzsch, 2002). Recently, we extended these studies by characterizing synaptic activity-induced Ca 2+ signaling and confirming mGluR-induced increase of intracellular Ca 2+ concentration in NM neurons (Wang et al, 2012). …”
Section: Anatomy and Physiology Of Mglurs In Avian Lower Auditory Bramentioning
confidence: 70%
“…Readers are referred to a comprehensive review covering these studies (Rubel and Fritzsch, 2002). Recently, we extended these studies by characterizing synaptic activity-induced Ca 2+ signaling and confirming mGluR-induced increase of intracellular Ca 2+ concentration in NM neurons (Wang et al, 2012). …”
Section: Anatomy and Physiology Of Mglurs In Avian Lower Auditory Bramentioning
confidence: 70%
“…For optimally performing auditory tasks across sound frequencies, auditory neurons develop gradients of structural, synaptic, and intrinsic properties along the tonotopic axis. In the auditory brainstem, frequency-specific neuronal processing is tuned by tonotopic gradients of ion channel expression ( von Hehn et al, 2004 ; Leao et al, 2006 ; Gazula et al, 2010 ), synaptic transmission and depression ( Köppl, 1994 ; Fukui and Ohmori, 2004 ; Slee et al, 2010 ; Oline and Burger, 2014 ), and inhibitory kinetics ( Tang et al, 2011 ; Wang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated expression of vGluT2 mRNA in AG neurons. Neurons in the magnocellular and angular nuclei evoke excitatory postsynaptic potentials mediated by AMPA and/or NMDA receptors by stimulation of the auditory nerve (Martin, ; Zhang and Trussell, ,b; MacLeod and Carr, ; Wang et al., ). Raman and Trussell () showed pharmacological evidence of kainate receptors in the magnocellular nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…They synapse on the auditory ganglion (AG) cells which in turn project to the magnocellular nucleus and angular nucleus in the brainstem (Boord and Rasmussen, ; Takasaka and Smith, ; Parks and Rubel, ). Stimulation of the chick auditory nerve evokes excitatory postsynaptic potentials in neurons of the magnocellular nucleus and angular nucleus mediated by α ‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole propionic acid (AMPA) and N‐methyl‐D‐aspartate (NMDA) receptors (Zhang and Trussell, ,b; Lawrence et al., ; MacLeod and Carr, ; Wang et al., ). Neurons in the magnocellular and angular nuclei express mRNAs or proteins of three types of glutamate receptors: AMPA, kainate and NMDA receptors (Levin et al., ; Reng et al., ; Parks, ; Karim et al., ).…”
Section: Introductionmentioning
confidence: 99%